Condição docente e adoecimento: pela não interdição do debate - RAMOS, Vanessa Parente (2023)
This text discusses aspects of Teaching Work from two concepts: condition and teacher illness, in a school in the city of Abaetetuba-PA. It aims to analyze the teaching condition of the subjects under study, the singularity of the illness and how the health care of professionals from the Municipal Education Network occurs from the perspective of two teachers. The theoretical framework is based on Oliveira (2010) to discuss the teaching profession, Izabel Reis (2012) to understand the teaching illness and Assunção and Oliveira (2009) to address the intensification, health and teaching condition. The methodology used was qualitative and exploratory in nature, with bibliographical and field research, using a semi-structured interview with two professors as an instrument. From the analysis carried out, it was possible to verify that the illness of the teachers of the interviewees is not the result of the activities of the profession, however the aggravation of the disease is related to the teaching condition, considering that the choice of function for readaptation in the work environment is carried out in a way random and does not consider the particularities of each disease. In addition, the Department of Education does not have a specific center to assist professionals in illness, this task being carried out by the Human Resources sector of the said body, in addition to not providing health insurance.